2012
DOI: 10.1007/s13361-012-0485-9
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Carry-Over in an Online Pepsin Digestion System used for the H/D Exchange Mass Spectrometric Analysis of an IgG1 Monoclonal Antibody

Abstract: Chromatographic carry-over can severely distort measurements of amide H/D exchange in proteins analyzed by LC/MS. In this work, we explored the origin of carry-over in the online digestion of an IgG1 monoclonal antibody using an immobilized pepsin column under quenched H/D exchange conditions (pH 2.5, 0°C). From a consensus list of 169 different peptides consistently detected during digestion of this large,~150 kDa protein, approximately 30 % of the peptic peptides exhibited carry-over. The majority of carry-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
1
65
0
Order By: Relevance
“…65 Three replicate sets of H/D-exchange data were processed using HDExaminer (Sierra Analytics, California). Each set of data was manually curated independently to minimize bias by the analyst.…”
Section: Methodsmentioning
confidence: 99%
“…65 Three replicate sets of H/D-exchange data were processed using HDExaminer (Sierra Analytics, California). Each set of data was manually curated independently to minimize bias by the analyst.…”
Section: Methodsmentioning
confidence: 99%
“…Three independent replicates for both protein concentrations were prepared and analyzed. To minimize peptide carryover in the immobilized pepsin column, the column was washed between samples following a cleaning procedure described previously 80 except that 2 cycles of pepsin column wash were used after each injection. Deuteration was measured using a time-of-flight mass spectrometer (Agilent 6220, Santa Clara, CA) equipped with a standard electrospray ionization source operated in positive mode.…”
Section: Circular Dichroismmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23], in the a2b helix, and the junction with the a3 helix (peptide [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and in the junction between a4b and a5 helices (peptide 104-116). Peptides were not identified for the central region of the a3 helix (residues [56][57][58][59][60][61][62][63][64][65][66][67][68] and the N-terminal half of the a5 helix (residues 121-125), hence the deuterium incorporation of these regions is unknown. Viewed in the context of the folded structure, the overall pattern of incorporation is clear [ Fig.…”
Section: Hdx-ms Of Cp149 Dmentioning
confidence: 99%
“…52,[58][59][60] Unfortunately, observation of EX1-type kinetics is often an artifact attributable either to chemical perturbation of the proteins, or to experimental error, such as carryover between injections. 61,62 Carryover was specifically avoided in our experiments by extensive washing of the pepsin and LC columns between sample injections (see Materials and Methods). In our HDX study, we identified in both Cp149 d and reduced Cp(210)149 d identical specific structural regions exhibiting a mixture of EX1-type and EX2-type kinetics.…”
Section: Comparing the Structural Regions Exhibiting A Bimodal Distrimentioning
confidence: 99%
See 1 more Smart Citation